Deformation Behavior of Elastomer-Glass Fiber-Reinforced Plastics in Dependence of Pneumatic Actuation - Mona Mühlich (Biomimetics, 2021)
This paper aims to define the influencing design criteria for compliant folding mechanisms with pneumatically actuated hinges consisting of fiber-reinforced plastic (FRP). Through simulation and physical testing, the influence of stiffness, hinge width as well as variation of the stiffness, in the flaps without changing the stiffness in the hinge zone, was evaluated. Within a finite element model software, a workflow was developed for simulations, in order to infer mathematical models for the prediction of mechanical properties and the deformation behavior as a function of the aforementioned parameters. In conclusion, the bending angle increases with decreasing material stiffness and with increasing hinge width, while it is not affected by the flap stiffness itself. The defined workflow builds a basis for the development of a predictive model for the deformation behavior of FRPs.